Analisis Perceived Usefulness, Perceived Ease of Use, dan Perceived Risk terhadap Minat Pembayaran Quick Response Code Indonesian Standard (QRIS) - Mohamad Sajili (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2025)
This research aims to determine perceptions regarding the use of QRIS as a digital-based payment system in Jakarta. The research method uses quantitative methods. This sample was taken using a questionnaire. The population in this sample is application users in Jakarta who use the QRIS application as a means of payment. The sample used in this questionnaire was 113 people, and the method of distributing the questionnaire was via Google Form which had been adjusted to the questions for each variable. Data analysis in this study used PLS-Sem. The research results show that there is a positive and significant influence between perceived ease of use and perceived usefulness on behavior of use. There is no influence between perception of security on behavior of use.